UV Spectrophotometric Method Development and Validation of Butorphanol Tartrate in Bulk Drug and Pharmaceutical Formulation - Ahirwar, Sonu; Kashaw, Varsha; Sahu, Ravish; Chourasia, Surbhi; Rajoria, Vaibhav; Kushwaha, Prakash (Journal of Drug Delivery and Therapeutics, 2024)
The present research work discusses the development and validation of a UV spectrophotometric method for butorphanol tartrate. Simple, accurate and cost efficient spectrophotometric method has been developed for the estimation of butorphanol tartrate in tablet dosage form. The optimum conditions for the analysis of the drug were established. The maximum wavelength (λ max) was found to be 278nm. The percentage recovery of butorphanol tartrate was in the 100.016±0.68. Beers law was obeyed in the concentration range of 2-12μg/ml. Calibration curves shows a linear relationship between the absorbance and concentration. The line equation y = 0.0674x - 0.0057 with r2 of 0.9998was obtained. Validation was performed according to ICH guidelines for linearity, accuracy, precision, LOD and LOQ. The sample solution was stable up to 36 hours. The proposed method may be suitable for the analysis of butorphanol tartrate in tablet formulation for quality control purposes. Keywords: Butorphanol tartrate, Validation, Precision, Accuracy, LOQ, LOD, ICH guidelines.